2021
DOI: 10.1093/jee/toab158
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila suzukii (Diptera: Drosophilidae): A Decade of Research Towards a Sustainable Integrated Pest Management Program

Abstract: Drosophila suzukii (Matsumura) (Diptera: Drosophilidae) also known as spotted-wing drosophila (SWD), is a pest native to Southeast Asia. In the last few decades, the pest has expanded its range to affect all major European and American fruit production regions. SWD is a highly adaptive insect that is able to disperse, survive, and flourish under a range of environmental conditions. Infestation by SWD generates both direct and indirect economic impacts through yield losses, shorter shelf life of infested fruit,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
117
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(149 citation statements)
references
References 322 publications
0
117
0
Order By: Relevance
“…The possibility to use plant-based chemicals as integrated pest management (IPM) solutions towards D. suzukii is not a novelty [ 15 , 64 ]. In fact, it has been observed that D. suzukii is susceptible to the toxic action of EOs and their components, in particular to limonene, carvacrol, thymol, and eugenol [ 23 , 25 , 26 , 31 , 32 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility to use plant-based chemicals as integrated pest management (IPM) solutions towards D. suzukii is not a novelty [ 15 , 64 ]. In fact, it has been observed that D. suzukii is susceptible to the toxic action of EOs and their components, in particular to limonene, carvacrol, thymol, and eugenol [ 23 , 25 , 26 , 31 , 32 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Drosophila suzukii (Matsumura) (Diptera: Drosophilidae), or spotted wing Drosophila (SWD), has successfully spread to Europe and the USA, but also South America, Canada, and Africa, from its areas of origin (China, Taiwan, and Korea) [ 13 , 14 , 15 , 16 ]. Small red fruits (such as blackberries, raspberries, and cherries) are the most affected, but D. suzukii can attack other species, such as olives, spicebush, and mistletoe [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gut contents analysis of wild caught flies would allow for real-time study of these effects. If mushroom, other fungi, and manure sources are used in the natural environment, removal of these resources or mitigation at these sites, particularly during the early spring months when fruit are scarce, may be beneficial (Tait et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It can be implemented by timely pest sampling/monitoring to estimate pest densities, being combined with judicious pesticide use and various "green" management methods including trapping and use of synthetic pheromones, biological control by conserving and/or releasing arthropod natural enemies, agronomic and cultural control through habitat manipulation and use of resistant crop varieties (Kogan 1998;Desneux et al 2007;Meissle et al 2011;Ragsdale et al 2011). To some extent, the need of IPM programs for invasive arthropod pests is comparable and even greater than that for endemic ones (Witzgall et al 2008;Ragsdale et al 2011;Haye et al 2016;Deligeorgidis et al 2019;Moreau et al 2019;Santoiemma et al 2020;Shah et al 2020;Gugliuzzo et al 2021;Tait et al 2021).…”
Section: Introductionmentioning
confidence: 99%